2014
DOI: 10.9790/1959-03310106
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status, Dietary Practices and Nutrition Related Beliefs of High School Girls in Urban Area of Bangalore City

Abstract: The study was conducted to explore the nutritional status, dietary practices and nutrition related beliefs of high school girls' age between twelve to seventeen years. One hundred and fifty high school girls from two government schools of Bangalore were selected for the study by stratified random sampling. The research design was descriptive analytical and cross sectional. A semi-structural questionnaire was used to collect the data on dietary practices and nutrition related beliefs and observational checklist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…This finding is similar with studies conducted in Mekelle town (6%) [ 8 ], Addis Ababa (8.5%) [ 21 ], Agarfa (8.96%) [ 18 ], and Chiro town (4.1%) [ 14 ]. However, it is higher than studies conducted in Hawassa (2.8%) [ 20 ] and Banglore city (3%) [ 9 ]. In contrast, it was lower than the findings from Bahir Dar (16.7%) [ 22 ], West Bengal (11.4%) [ 10 ], and America (69%) [ 23 ].…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…This finding is similar with studies conducted in Mekelle town (6%) [ 8 ], Addis Ababa (8.5%) [ 21 ], Agarfa (8.96%) [ 18 ], and Chiro town (4.1%) [ 14 ]. However, it is higher than studies conducted in Hawassa (2.8%) [ 20 ] and Banglore city (3%) [ 9 ]. In contrast, it was lower than the findings from Bahir Dar (16.7%) [ 22 ], West Bengal (11.4%) [ 10 ], and America (69%) [ 23 ].…”
Section: Discussionmentioning
confidence: 63%
“…This is comparable with studies conducted in Addis Ababa (6.2%) [ 13 ] and Bahir Dar (8.6%) [ 19 ]. However, it was lower than studies conducted in Amhara region (13.6%) [ 16 ], Tigray Region (21.4%) [ 19 ], Chiro town (24.4%) [ 14 ], Hawassa (12.9%) [ 20 ], Timor-Leste (49.2%) [ 1 ], Bangalore city (69.2%) [ 9 ], and West Bengal (11.3%) [ 10 ]. This variation could be due to cultural difference in dietary habit and caring practices.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…4 The link between dietary practices and nutritional status has been widely reported in literature. [27][28][29] A study among Ethiopian adolescent girls revealed that girls with higher dietary diversity score were more likely to have normal BMI-for age Z score than those with low dietary diversity score. 30 It has further been reported that poor dietary diversity during childhood characterized by overconsumption of starchy staples is associated with childhood malnutrition and triples the risk for diabetes mellitus in rural Kenya.…”
Section: Dietary Practicesmentioning
confidence: 99%
“…Low body mass index (BMI) is 53% in India and 36% in Nepal. 10,11 A large numbers of adolescent girls are suffering from malnutrition both in urban and rural areas of Bangladesh. The prevalence of adolescent's stunting is 36% and low body mass index (BMI) is 50% in Bangladesh.…”
mentioning
confidence: 99%